Sustainability as a Trend in the Fashion Market (ModaPalavra e-periódico, 2018)
The themes related to sustainability have grown significantly in recent times in all areas of studies and marketing. In this context, the fashion industry, one of the most polluting in the world, has been promoting changes in the mode of operation of its activities, seeking to find solutions within a complex chain, aiming to effectively manage the consequences caused in society to the detriment of its activity. Based on a qualitative bibliographical study, this work seeks to identify sustainability as a current trend in the fashion market, since it is a rising theme in the academic and marketing area, analyzing the issues involved and also self-styled sustainable fashion brands.
Keywords: trend studies; fashion industry; sustainability